Analysis of Accident-Prone Areas in The Alianyang-Pangeran Natakusuma-Danau Sentarum Road Corridor, Pontianak - Ayunda, Nurul Alya; Kadarini, S. Nurlaily; Azwansyah, Heri (Jurnal Teknik Sipil, 2024)
Accidents are often caused by poor road equipment, such as damaged signs and markings, poor road conditions, and substandard road geometry. This study aims to identify traffic accident characteristics, determine accident-prone areas, and recommend safety improvements along the Jalan Alianyang-Jalan Pangeran Natakusuma-Jalan Danau Sentarum corridor in Pontianak. It utilizes secondary data from the Pontianak Police (2018-2023) and primary data from field surveys. Accident characteristics were analyzed to calculate accident-prone areas (black sites) using the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods. The study found a black site in Segment 5 (intersection of Jalan Dr. Sutomo and Jalan Pak Benceng) with an EAN value of 66, exceeding the UCL of 62. Minor injuries were the most common, with 52 victims, and accidents frequently occurred on Saturdays, especially between 12:00-17:59. Most accidents involved males (29 people), with front-side collisions being the most common type (9 events). Recommendations include installing crossing warning signs and maintaining road markings.Keywords: Accident-Prone Area, Black site, Equivalent Accident Number, Upper Control Limit. Poor Road Condition